Midwives' experience of delivering a counselling intervention to distresses postnatal women - Reed, Maree (Curtin University, 2012)
‘Promoting resilience in mothers’ emotions’ (PRIME) was a large, team-based NHMRC funded randomised control trial (RCT) aimed at determining the effectiveness of a midwife-led counselling intervention in minimising psychological distress in childbearing women. Midwives were employed as research assistants and trained to deliver a counselling intervention to distressed postnatal women. This present study made use of an opportunity to explore and describe these midwives’ experiences.The purpose of this qualitative descriptive exploratory study was to explore and describe midwives’ (n=18) experiences of working as research assistants in the PRIME project as well as their experiences of learning and delivering a midwife-led counselling intervention to distressed postnatal women. In-depth interviews, midwife diary entries and their postings on the PRIME midwifery forum were the methods of data collection employed for this study. Data was analysed using manual thematic analysis techniques. There were two distinct findings elicited from the midwives’ descriptions.The first related to the challenging but worthwhile nature of their role as research assistants. Midwives in this study considered their preparation for and work as a research assistant in the RCT a challenging experience. In part, they attributed this to learning the counselling intervention, having their practice critiqued and being daunted by the level of commitment the research role required of them. The support of the collegial team members of the project was therefore fundamental to the midwives perceiving this experience positively. Despite these challenges, midwives expressed that overall PRIME was a worthwhile experience that enhanced their knowledge of the research process.The second finding was the level of confrontation midwives experienced as they came to appreciate the level of emotional distress some women suffered as a consequence of their birth experience. A desire to improve the emotional care provided to women in the postpartum was the midwives’ primary motivation to contribute to the PRIME project. Midwives wanted to be more actively involved in the care of women distressed by their birthing events, however it was evident that prior to PRIME many were not confident in their ability to perform this role.For the most part, they attributed this lack of confidence on insufficient counselling education received in their midwifery training, limited opportunity to impart emotional care in practice and the subsequent delegation of women’s emotional care to other health professionals. Although considered challenging for most of the midwives to learn, the advanced counselling skills they acquired in PRIME provided them the confidence to care for women distressed by their birthing experience and to personally deal with any stressful situations they may encounter in practice. The findings of this study contribute to developing a better understanding of midwives’ experiences of participating in research and working with distressed women in practice.